2021
DOI: 10.1088/1755-1315/761/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of ImageJ, Leaf Doctor Applications, and Visual Assessments in Measuring Severity of Two Leaf Spot Diseases

Abstract: In this research, reliability for disease severity assessment was compared for two different digital imaging quantifying techniques (ImageJ and Leaf Doctor applications) and visual assessments included ImageJ (IJ), Leaf Doctor (LD) applications, and visual assessments (VA) for the downy mildew of lettuce and Cercospora leaf spot of chard. Samples of infected chard leaves with symptoms of Cercospora leaf spot disease and lettuce leaves with symptoms of downy mildew were randomly collected from a field and a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…It is an application specially developed to evaluate leaf damage and makes the work faster and easier than the rather complicated ImageJ program. Similarly, Alheeti et al (2021) indicated that the use of ImageJ to assess leaf infection by two fungal pathogens is more laborious than the Leaf Doctor application (free application for iPhone) (Pethybridge and Nelson, 2015). The development of plug-ins for ImageJ may be a solution to this problem.…”
Section: Resultsmentioning
confidence: 99%
“…It is an application specially developed to evaluate leaf damage and makes the work faster and easier than the rather complicated ImageJ program. Similarly, Alheeti et al (2021) indicated that the use of ImageJ to assess leaf infection by two fungal pathogens is more laborious than the Leaf Doctor application (free application for iPhone) (Pethybridge and Nelson, 2015). The development of plug-ins for ImageJ may be a solution to this problem.…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of disease symptoms is critical for evaluating disease severity, and it is a prerequisite for making the best disease management decisions [ 46 ]. Based on the visual assessment, we initially selected PM sensitive, moderate resistant, and resistant lines on a scale of 1–9.…”
Section: Resultsmentioning
confidence: 99%
“…Para observar el comportamiento de los síntomas durante las fases fenológicas del cultivo y el efecto de la aplicación de la fertilización, se realizaron colectas de hojas de tres plantas en cada línea de arroz a los 30, 60 y 90 DDS. La severidad de los síntomas se obtuvo siguiendo la metodología empleada por Alheeti et al (2021) con algunas modificaciones al colocar nueve hojas sobre un Escáner Epson Perfection V39, obtenidas de tres plantas al azar, de cada planta se extrajo tres hojas (una hoja del estrato inferior, una hoja del estrato medio y una hoja del estrato superior), junto con una unidad de medida en cm. Posteriormente, las imágenes digitales se cargaron al software ImageJ V 1.8.0 en el cual se midió el área foliar total (AFT) y el área foliar dañada (AFD) por síntomas de hongos fitopatógenos.…”
Section: Severidad De Síntomas Causados Por Hongos Fitopatógenosunclassified